Home education in the face of the XXI century plague first „waves” - Marek Budajczak (Studia z Teorii Wychowania)
The article presents, along with the necessary definitions and a sketchy, pre-pandemic history of home education, its quantitative and qualitative situation in the conditions of a pandemic in Poland and several other countries, against the background of a few selected dimensions of the functioning of state education systems and schools.